Quality of life in patients with liver metastases from colorectal cancer treated with first-line selective internal radiotherapy (SIRT): Results from the FOXFIRE prospective randomized studies - Gray, A; Wolstenholme, J; Fusco, F; Chau, I; Dunham, L; Love, S; Roberts, A; Moschandreas, J; Virdee, P; Lewington, V; Wilson, G; Tait, P; et al. (Oxford University Press, 2017)
Quality of life (QoL) in patients with colorectal cancer and liver metastases treated with selective internal radiotherapy (SIRT) using Yttrium-90 resin microspheres combined with FOLFOX (standard chemotherapy) has not been compared to FOLFOX alone. We report QoL results from a prospectively pooled analysis of 3 multicentre randomized trials: FOXFIRE, FOXFIRE-Global and SIRFLOX.